Photovoltaic and Wind Energy Conversion Systems - Figueres, Emilio (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
In the first decades of the current millennium, the contribution of photovoltaic and wind energy systems to power generation capacity has grown extraordinarily all around the world; in some countries, these systems have become two of the most relevant sources to meet the needs of energy supply. This Special Issue deals with all aspects of the development, implementation, and exploitation of systems and installations that operate with both sources of energy.